Characterization of conformationally constrained benzanilide scaffolds for potent and selective HDAC8 targeting - Hassan, Muhammad Murtaza; Israelian, Johan; Nawar, Nabanita; Ganda, Giovanni; Manaswiyoungkul, Pimyupa; Raouf, Yasir S.; Armstrong, David; Sedighi, Abootaleb; Olaoye, Olasunkanmi O.; Erdogan, Fettah; Cabral, Aaron D.; Angeles, Fabrizio; et al. (Journal of medicinal chemistry, 2020)
Histone deacetylases (HDACs) are an attractive therapeutic target for a variety of human diseases. Currently, all four FDA-approved HDAC-targeting drugs are nonselective, pan-HDAC inhibitors, exhibiting adverse side effects at therapeutic doses. Although selective HDAC inhibition has been proposed to mitigate toxicity, the targeted catalytic domains are highly conserved. Herein, we describe a series of rationally designed, conformationally constrained, benzanilide foldamers which selectively bind the catalytic tunnel of HDAC8. The series includes benzanilides, MMH371, MMH409, and MMH410, which exhibit potent in vitro HDAC8 activity (IC50 = 66, 23, and 66 nM, respectively) and up to 410-fold selectivity for HDAC8 over the next targeted HDAC. Experimental and computational analyses of the benzanilide structure docked with human HDAC8 enzyme showed the adoption of a low-energy L-shaped conformer that favors HDAC8 selectivity. The conformationally constrained HDAC8 inhibitors present an alternative biological probe for further determining the clinical utility and safety of pharmacological knockdown of HDAC8 in diseased cells.
Gesehen am 25.09.2020